Seismic Performance Comparison of Simply Supported Hollow Slab on Pile Group Structure with Different Operational Category and Shear Panel Damper Application - Yusuf Haroki; Ali Awaludin; Henricus Priyosulistyo; Angga Fajar Setiawan; Iman Satyarno (Civil Engineering Dimension, 2023)
This study is aimed to compare the seismic performance of simply supported hollow slab on pile group (SHSPG) structures designed as “critical” and “essential” viaducts with shear panel damper (SPD) devices. There were three numerical models to be compared, namely SHSPG-A, SHSPG-B, and SHSPG-C. SHSPG-A is a “critical” viaduct with 35 piles per one pile head. SHSPG-B is an “essential” viaduct with 18 piles per one pile head. SHSPG-C is an “essential” viaduct with 18 piles per one pile head plus sixteen SPDs. Numerical models considered the prestressing effect of the spun pile. Nonlinear time history analyses were executed using seven pairs of recorded ground motions that had been scaled and adjusted to the seismic characteristics of Yogyakarta, Indonesia. As the result, the performance level of SHSPG-A was much better than SHSPG-B. The SPDs application could maintain SHSPG-C’s performance at the same level as SHSPG-A and dissipate 34.28%-53.03% of the seismic energy.